Successful secure high-definition streaming telecytology for remote cytologic evaluation - Sahussapont Joseph Sirintrapun; Dorota Rudomina; Allix Mazzella; Rusmir Feratovic; Oscar Lin (Elsevier, 2017)
Background: The use of minimally invasive procedures to obtain material for diagnostic purposes has become more prevalent in recent years. As such, there is increased demand for immediate cytologic adequacy assessment of minimally invasive procedures. The array of different locations in which rapid on-site evaluation (ROSE) is expected requires an ever-increasing number of cytology personnel to provide support for adequacy assessment. In our study, we describe the implementation process of a telecytology (TC) system in a high case volume setting and evaluate the performance of this activity. Methods: We performed retrospectively an analysis of all consecutive remote TC ROSE evaluations obtained for 15 months. The specimens were evaluated using a TC system. The ROSE adequacy assessment obtained at the time of the procedure was compared to the final cytopathologist-rendered adequacy assessment when all the material was available for review, including the alcohol-fixed preparations. Results: A total of 8106 distinct cases were analyzed. TC-assisted preliminary adequacy assessment was highly concordant with the final cytopathologist-rendered adequacy assessment. Perfect concordance or accuracy was at 93.1% (7547/8106). The adequacy upgrade rate (inadequate specimen became adequate) was 6.8% (551/8106), and the initial adequacy downgrade (adequate specimen became inadequate) was <0.1% (8/8106). Conclusions: The TC outcome demonstrates high concordance between the initial adequacy assessment and final cytopathologist-rendered adequacy assessment. Adequacy upgrades were minor but, more importantly, our results demonstrate a minimal adequacy downgrade. The process implemented effectively eliminated the need for an attending pathologist to be physically present onsite during a biopsy procedure.